Mortality and Financial Burden of Periprosthetic Fractures of the Femur. (December 2014) - Shields, Edward; Behrend, Caleb; Bair, Jeff; Cram, Peter; Kates, Stephen
Objective: This study examines patient factors to identify risks of 12-month mortality following periprosthetic femur fractures. Hospital charges were analyzed to quantify the financial burden for treatment modalities. Methods: Data were retrospectively analyzed from a prospective database at a university hospital setting. One-hundred and thirteen patients with a periprosthetic fracture of the proximal or distal femur were identified. Risk factors for 12-month mortality were analyzed, and financial data were compared between the various treatment modalities. Results: In all, 14% of patients died (16 of 113) within 3 months and the 1-year mortality was 17.7% (20 of 113). Patients who died within 1 year had higher hospital charges (US$33 880 ± 25 051 vs US$22 886 ± 16 841; P = .01) and were older (87.6 ± 8.5 vs 81.5 ± 8.6; P = .004). Logistic regression analysis revealed age was the only significant predictor of 1-year mortality ( P = .029, odds ratio 1.1). Analysis of financial data revealed 4 distinct groups ( P < .05 between groups). Distal femoral revision arthroplasty (RA-DF) generated the highest hospital charges of US$91 035 ± 25 579 (n = 3). The second most highly charged group included proximal femoral fractures treated with revision arthroplasty (US$34 078 ± 17 832; n = 20) and hemi/total hip arthroplasty (THA; US$41 556 ± 23 651; n = 8). The third most charged group underwent open reduction internal fixation of the proximal (US$18 706 ± 6829; n = 35) and distal (US$22 381 ± 10 835; n = 35) femur. Nonoperative treatment generated the lowest charges (US$6426 ± 2899; n = 11). On average, the hospital lost money treating patients with RA-DF (US$−19 080 ± 2022 per patient) and hemi/THA (US$−6594 ± 9305 per patient), while all other treatment groups were profitable. Conclusion: One-year mortality after periprosthetic femur fractures was 17.7%, is mostly influenced by age, and 80% of deaths occur within 3 months. Patients treated with primary/revision arthroplasty generate more hospital charges than internal fixation. The average patient treated with revision arthroplasty of the distal femur or hemi/THA for a periprosthetic femur fractures resulted in net financial losses for the hospital.